Metodología para evaluación de la seguridad vial a la infraestructura de usuarios vulnerables (peatones, ciclistas y motociclistas) en proyectos viales concesionados. Caso de estudio autopista Bogotá-Villeta del km 0+000 al km 5+000 (2017)
As is general knowledge, it is necessary to establish safety parameters for all users of the road, taking into account that the most affected with the increase of lanes on a national road are vulnerable users (motorized and non-motorized) because the priority of the contractors, contractors, designers and builders are not the safety conceived in an integral way, including light and heavy vehicles, pedestrians, cyclists and motorcyclists, but the times of diminution between a point of departure and one of arrival, thus leaving aside the third users of the roads, which are pedestrians, cyclists and motorcyclists. The current government, through the promulgation of the National Road Safety Plan 2011-2021, declared for the first time in the history of Colombia road safety as a State policy, calling on the entire international community to declare this as the decade of action in road safety, which transcends the plans and programs of a period of government. As frequent users of existing road corridors, we evidence the imprudence of drivers of vehicles, as well as that of vulnerable users when sharing a space that has only been designed for vehicle traffic, because the priorities are not defined, they are not met the established traffic rules, the existing traffic signs and the infrastructure failure for the free movement of vulnerable users are not respected. The above generates conflicts that must be solved in conjunction with the entities involved in the construction and maintenance of the roads, to reduce the percentage of accident rate with vulnerable users involved that is currently evident and that each day increases, with the proposed study section being evidence clear of this problem.